Diffuse Alveolar Hemorrhage Associated with Warfarin Therapy - Bülent Kaya; Ibrahim Yildiz; Reshat Mehmet Baha; Neslihan Ebru Eryaşar Zeytun; Azize Yetisgen (Case Reports in Medicine)
Diffuse alveolar hemorrhage (DAH) is a life-threatening clinical pathologic syndrome caused by a variety of diseases. We report a case of DAH related to therapy of warfarin use. In this case report, we present the diffuse alveolar hemorrhage case as a rare and life-threatening complication of warfarin.